Răspunsuri

Cel mai inteligent răspuns!
2014-07-29T10:28:34+03:00
X*y= xy+4x+4y+12
(x*y)*z = x*(y*z)
   t                t
ms= (x*y)*z= tz+4t+4z+12=(xy+4x+4y+12)z+4(xy + 4x+4y+12) +4z+12
           t 
                                       = xyz + 4xz+4yz+12z+4xy+16x+16y+48+4z+12
                                       = xyz+4xz+4yz+4xy+16x+16y+16z+60

md= x*(y*z) = xt+4x+4t+12=x(yz+4y+4z+12) +4x+4(yz+4y+4z+12)+12
              t
                                         = xyz+4xy+4xz+12x+4x+4y+4yz+16y+16z+18+12
                                         = xyz+4xy+4xz+4yz+16x+16y+16z+60
             => „*” este asociativă

1 5 1